Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
Through the carbon material design under specific conditions, the challenges in energy density and charging time of the negative electrode material of lithium-ion secondary battery are solved, and the input and output characteristics and cycle characteristics are improved, which extends the battery life and improves the high-temperature storage capacity.
Patent Information
- Application Number
- CN202411373207.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-05
- Publication Date
- 2024-12-27
AI Technical Summary
The negative electrode materials of the existing lithium-ion secondary batteries are prone to problems such as lithium precipitation and reduced circulation characteristics while increasing the energy density and shortening the charging time.
Specific carbon materials are used to meet certain particle size distribution, specific surface area ratio and tap density to improve input and output characteristics and cyclic characteristics, including spherical carbon materials to reduce pressing pressure and suppress void blockage.
It realizes excellent input and output characteristics and cycle characteristics of lithium-ion secondary batteries, extends the service life of the battery and improves the high-temperature storage characteristics.
Smart Images

Figure BDA0005068102280000231 
Figure BDA0005068102280000232 
Figure BDA0005068102280000241
Abstract
Description
[0001] The present invention is a divisional application of the invention application with application number 202180075249.7 (international application number PCT / JP2021 / 014523), application date April 5, 2021, and invention name “Negative electrode material for lithium-ion secondary battery, negative electrode for lithium-ion secondary battery, and lithium-ion secondary battery”. Technical Field
[0002] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery. Background Art
[0003] Lithium-ion secondary batteries have been widely used in electronic devices such as notebook personal computers (PCs), mobile phones, smart phones, and tablet PCs due to their small size, light weight, and high energy density. In recent years, against the backdrop of environmental issues such as global warming caused by CO2 emissions, electric vehicles such as clean electric vehicles (EVs) that use only batteries for driving, hybrid electric vehicles (HEVs) that combine gasoline engines and batteries, and plug-in hybrid electric vehicles (PHEVs) have become increasingly popular, and the development of lithium-ion secondary batteries (on-board lithium-ion secondary batteries) as batteries for these electric vehicles is being promoted.
[0004] The performance of the negative electrode material of lithium-ion secondary batteries has a great influence on the characteristics of lithium-ion secondary batteries. Carbon materials are widely used as materials for negative electrode materials for lithium-ion secondary batteries. The carbon materials used in negative electrode materials are roughly divided into graphite and carbon materials with lower crystallinity than graphite (amorphous carbon, etc.). Graphite has a structure composed of hexagonal mesh planes of carbon atoms stacked in an orderly manner. When it is made into the negative electrode material of lithium-ion secondary batteries, lithium ions are inserted and separated from the ends of the hexagonal mesh planes to perform charging and discharging.
[0005] The stacking of the hexagonal mesh of amorphous carbon is irregular or does not have a hexagonal mesh. Therefore, in the negative electrode material using amorphous carbon, the insertion and separation reaction of lithium ions is carried out on the entire surface of the negative electrode material. Therefore, compared with the case where graphite is used as the negative electrode material, it is easy to obtain a lithium ion battery with excellent input and output characteristics (for example, referring to patent document 1 and patent document 2). On the other hand, amorphous carbon has a lower energy density than graphite because its crystallinity is lower than that of graphite.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 4-370662
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 5-307956
[0010] Patent Document 3: International Publication No. 2012 / 015054 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Taking into account the characteristics of the above-mentioned carbon materials, the following negative electrode material has also been proposed: amorphous carbon and graphite are composited to improve the input-output characteristics while maintaining a high energy density, and by setting the graphite to a state of being coated with amorphous carbon to reduce the surface reactivity, the input-output characteristics are improved while maintaining a good initial charge and discharge efficiency (for example, refer to patent document 3).
[0013] For lithium ion secondary batteries used in EV, HEV, etc., high energy density is required from the perspectives of driving comfort, long-distance continuous driving, etc. High energy density lithium ion secondary batteries require shortening the charging time. In order to shorten the charging time of lithium ion secondary batteries, it is necessary to increase the current density. However, in order to fill the lithium ion secondary battery in a short time and increase the current density, there is a tendency that lithium precipitation is easy to occur in the negative electrode, and the input characteristics, cycle characteristics, etc. deteriorate.
[0014] Since the high energy density of lithium ion secondary batteries can be achieved by increasing the amount of lithium ions that can be charged and discharged, the thick film of the negative electrode has been studied. However, in the case of wanting to achieve the high energy density of lithium ion secondary batteries by thick film of the negative electrode, the initial stage of the charge and discharge cycle is high capacity, but by repeated charge and discharge, SEI (solid electrolyte interface, Solid Electrolyte Interphase) film gradually grows. Thus, the gaps in the negative electrode are blocked and the mobility of lithium ions is impaired, and as a result, the cycle characteristics are easily reduced.
[0015] An object of one embodiment of the present invention is to provide a negative electrode material for a lithium ion secondary battery and a negative electrode for a lithium ion secondary battery, which can produce a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics.
[0016] Furthermore, an object of one embodiment of the present invention is to provide a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics.
[0017] Methods for solving problems
[0018] Specific methods for solving the above-mentioned problems include the following aspects.
[0019] <1> A negative electrode material for a lithium ion secondary battery, comprising a carbon material satisfying the following (1) and (2).
[0020] (1) D90 / D10 of the volume-based particle size is greater than 2.0 and less than 4.3.
[0021] (2) The value obtained by dividing the number of particles N with an equivalent circle diameter of 5 μm or less out of the total number of particles measured (10,000 particles) by the specific surface area S determined by nitrogen adsorption measurement at 77 K, that is, N / S is greater than or equal to 750 (particles·g / cm 2 ).
[0022] <2> The negative electrode material for a lithium ion secondary battery according to <1>, wherein the carbon material satisfies the following (3).
[0023] (3) The ratio of the number of particles having an equivalent circle diameter of 5 μm or less based on the number of particles is greater than or equal to 45% with respect to the total number of 10,000 particles measured.
[0024] <3> The negative electrode material for a lithium ion secondary battery according to <1> or <2>, wherein the carbon material satisfies the following (4).
[0025] (4) When X is set to the equivalent circle diameter calculated on a number basis at the cumulative 99% of the particle size distribution defined as a particle size greater than or equal to 5 μm, and Y is set to the circularity at the cumulative 1% of the circularity distribution defined as a particle size greater than or equal to 5 μm, the following formula (a) is satisfied.
[0026] Y≥0.3×log 10 (X)+(0.5-0.3×log 10 6)…(a)
[0027] <4> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <3>, wherein the carbon material satisfies the following (5).
[0028] (5) Tap density is 0.80 g / cm 3 ~0.95g / cm 3 .
[0029] <5> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <4>, wherein the carbon material satisfies the following (6).
[0030] (6) The average circularity is 0.90 to 0.93.
[0031] <6> The negative electrode material for lithium ion secondary batteries according to any one of <1> to <5>, wherein the carbon material has an average interplanar spacing d 002 for
[0032] <7> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <6>, wherein an R value of the carbon material as measured by Raman spectroscopy is 0.1 to 0.4.
[0033] <8> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <7>, wherein the carbon material has a specific surface area of less than or equal to 14 m2 as determined by nitrogen adsorption at 77 K. 2 / g.
[0034] <9> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <8>, wherein the carbon material does not have two or more exothermic peaks in a temperature range of 300° C. to 1000° C. in differential thermal analysis in an air flow.
[0035] <10> A negative electrode for a lithium ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium ion secondary battery according to any one of <1> to <9>.
[0036] <11> A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to <10>, a positive electrode, and an electrolyte.
[0037] Effects of the Invention
[0038] One embodiment of the present invention can provide a negative electrode material for a lithium ion secondary battery and a negative electrode for a lithium ion secondary battery, which can produce a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics.
[0039] Furthermore, one embodiment of the present invention can provide a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics. DETAILED DESCRIPTION
[0040] Hereinafter, the mode for implementing the present invention is described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, its constituent elements (also comprising element steps, etc.) are not necessary except for the cases specifically indicated. It is also the same about numerical value and its range, and does not limit the present invention.
[0041] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.
[0042] In the present disclosure, a numerical range expressed using "to" includes the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0043] In the numerical ranges recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in the present disclosure, the upper limit or lower limit of its numerical range can also be replaced by the value shown in each test.
[0044] In the present disclosure, each component may include a plurality of substances corresponding to each component. When a plurality of substances corresponding to each component are present in the composition, the content or content of each component refers to the total content or content of the plurality of substances present in the composition unless otherwise specified.
[0045] In the present disclosure, particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component exist in the composition, unless otherwise specified, the particle size of each component refers to the value for the mixture of the multiple types of particles present in the composition.
[0046] In the present disclosure, the term "layer" includes not only a case where the layer is formed in the entire region when the region where the layer exists is observed, but also a case where the layer is formed in only a part of the region.
[0047] In the present disclosure, the term "stacked" means stacking layers, and two or more layers may be combined or two or more layers may be detachable.
[0048] <Negative electrode materials for lithium-ion secondary batteries>
[0049] A negative electrode material for a lithium ion secondary battery comprising a carbon material satisfying the following (1) and (2).
[0050] (1) D90 / D10 of the volume-based particle size is greater than 2.0 and less than 4.3.
[0051] (2) The value obtained by dividing the number of particles N with an equivalent circle diameter of 5 μm or less out of the total number of particles measured (10,000 particles) by the specific surface area S determined by nitrogen adsorption measurement at 77 K, that is, N / S is greater than or equal to 750 (particles·g / cm 2 ).
[0052] When the negative electrode material for a lithium ion secondary battery satisfies the above (1) and (2), a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics can be produced. The reason for this is not clear, but it is presumed as follows.
[0053] In the above (1), D90 / D10 is greater than 2.0 and less than 4.3, so there is a tendency that the filling property of the carbon material is high. As a result, the electrode density when the negative electrode material for lithium ion secondary batteries is applied to the collector becomes higher, and there is a tendency that the pressing pressure required to obtain the target electrode density of the negative electrode for lithium ion secondary batteries can be reduced. By reducing the pressing pressure, the lateral orientation of the carbon material becomes lower, and lithium ions are easy to enter and exit during charging and discharging, resulting in a tendency to manufacture lithium ion secondary batteries with better input and output characteristics. In particular, the spheroidized graphite obtained by spheroidizing natural graphite is prone to produce hollow particles during the spheroidization process, and the hollow particles are deformed by the pressing pressure and are prone to lateral orientation. On the other hand, in the negative electrode material for lithium ion secondary batteries disclosed in the present invention, since the pressing pressure required to obtain the target electrode density can be reduced, even if the carbon material contained in the negative electrode material is spheroidized graphite, the increase in the lateral orientation of the carbon material can be suppressed.
[0054] In the above (1), when D90 / D10 is less than 4.3, the hindrance of the flow of liquid in the gaps between the carbon materials can be suppressed. This tends to enable the production of a lithium ion secondary battery having excellent input-output characteristics and cycle characteristics.
[0055] In (2) above, the number of particles N whose equivalent circle diameter based on number is less than or equal to 5 μm out of the total number of measured particles 10,000 indicates that more carbon materials have small particle sizes. If more carbon materials have small particle sizes, there is a tendency that the diffusion distance of lithium ions in the solid is short, and the output characteristics become good. Furthermore, in (2) above, the specific surface area S increases inversely proportional to the particle size of the carbon material, and there is a tendency that the input and output characteristics of the lithium ion secondary battery are further improved. However, electrolytic reaction is likely to occur at the interface between the carbon material with a large specific surface area and the electrolyte, and current concentration is likely to occur due to liquid depletion of the electrolyte. As a result, lithium precipitation is likely to occur, and the cycle characteristics are likely to be reduced.
[0056] In the negative electrode material for lithium ion secondary battery disclosed in the present invention, the ratio of the number of particles N to the specific surface area S, i.e., N / S, is set to be greater than or equal to 750 (particles·g / cm 2 ), so that the above-mentioned particle number N and specific surface area S are in an optimal balance. In this way, it is possible to suppress the reduction of the cycle characteristics of the lithium ion secondary battery while improving the input and output characteristics of the lithium ion secondary battery.
[0057] It should be noted that excellent input-output characteristics are synonymous with low resistance, and have the effect of suppressing heat generation caused by resistance. Therefore, by improving the input-output characteristics of lithium-ion secondary batteries, it is expected that high-temperature storage characteristics can be improved by suppressing heat generation.
[0058] Generally speaking, in lithium-ion secondary batteries, carbon materials repeatedly expand and contract due to charge and discharge, so the conduction path is easily disconnected due to interface peeling between the carbon material and the collector, peeling between carbon materials, etc. Furthermore, the cycle characteristics of lithium-ion secondary batteries may be reduced due to the reduction of charge and discharge capacity caused by deactivated negative electrode active materials and the increase of current density in effective negative electrode active materials.
[0059] On the other hand, in the negative electrode material for lithium ion secondary batteries disclosed in the present invention, by satisfying the above (1) and (2), there is a tendency to increase the contact points between the carbon material as the negative electrode active material and the collector, and between the carbon materials. By using the negative electrode material for lithium ion secondary batteries disclosed in the present invention, even when the carbon material is repeatedly expanded and contracted due to charge and discharge, it is possible to manufacture a lithium ion secondary battery that is suitable for maintaining the conductive path between the carbon material and the collector, the conductive path between the carbon materials, etc. As described above, there is a tendency to manufacture lithium ion secondary batteries with excellent life characteristics such as cycle characteristics, input and output characteristics, etc.
[0060] [Carbon material]
[0061] The negative electrode material for lithium ion secondary battery disclosed in the present invention (hereinafter, also referred to as "negative electrode material") includes a carbon material satisfying the above (1) and (2) (hereinafter, also referred to as "specific carbon material"). The content of the specific carbon material in the negative electrode material is not particularly limited, for example, it is preferably greater than or equal to 50% by mass, more preferably greater than or equal to 80% by mass, further preferably greater than or equal to 90% by mass, and particularly preferably 100% by mass.
[0062] The negative electrode material may also include other carbon materials other than the specific carbon material. As other carbon materials, there are no particular restrictions, and examples thereof include natural graphite such as scaly, earthy, and spherical graphite, graphite such as artificial graphite, amorphous carbon, carbon black, fibrous carbon, nanocarbon, etc. Other carbon materials may be used alone or in combination of two or more. In addition, the negative electrode material may also include particles containing elements that can absorb / release lithium ions. As elements that can absorb / release lithium ions, there are no particular restrictions, and examples thereof include Si, Sn, Ge, In, etc.
[0063] The volume-based particle size ratio D90 / D10 of the specific carbon material is greater than 2.0 and less than 4.3.
[0064] From the viewpoint of obtaining a lithium ion secondary battery with high capacity retention rate and excellent cycle characteristics by easily ensuring the conductive path between the carbon material and the collector, the conductive path between the carbon materials, etc., and from the viewpoint of easily improving the tap density, D90 / D10 is preferably greater than 2.2, more preferably greater than 2.5, and further preferably greater than 3.0.
[0065] From the viewpoint of appropriately suppressing the hindrance of the liquid flow in the gaps between the carbon materials and obtaining a lithium ion secondary battery with better input-output characteristics and cycle characteristics, the ratio is preferably less than 4.1, and more preferably less than 3.6.
[0066] The value of D90 / D10 may be changed within the above range in consideration of the amount of the negative electrode material composition applied to the current collector, the thickness of the negative electrode, and the like.
[0067] The particle size (D10) of the carbon material is the particle size at which the cumulative volume is 10% when the volume cumulative distribution curve is drawn from the small diameter side in the particle size distribution of the carbon material. The particle size (D90) of the carbon material is the particle size at which the cumulative volume is 90% when the volume cumulative distribution curve is drawn from the small diameter side in the particle size distribution of the carbon material. The particle size (D10) and the particle size (D90) can be measured by dispersing the carbon material in distilled water containing a surfactant and using a laser diffraction particle size distribution measuring device (e.g., SALD-3100 manufactured by Shimadzu Corporation).
[0068] The average particle size (D50) of the specific carbon material is preferably 22 μm or less.
[0069] From the perspective of suppressing the increase in the diffusion distance of lithium from the surface to the inside of the negative electrode material and further improving the input-output characteristics of the lithium-ion secondary battery, the average particle size (D50) of the specific carbon material is preferably less than or equal to 21 μm, and more preferably less than or equal to 20 μm.
[0070] From the perspective of suppressing the reduction in high-temperature storage characteristics of lithium-ion secondary batteries due to an increase in specific surface area, the average particle size (D50) of the specific carbon material is preferably greater than or equal to 10 μm, more preferably greater than or equal to 12 μm, further preferably greater than or equal to 15 μm, and particularly preferably greater than or equal to 17 μm.
[0071] The average particle size (D50) of the carbon material is the particle size when the cumulative volume distribution curve is drawn from the small diameter side in the particle size distribution of the carbon material. The average particle size (D50) can be measured by dispersing the carbon material in distilled water containing a surfactant and using a laser diffraction particle size distribution measuring device (for example, SALD-3100 manufactured by Shimadzu Corporation).
[0072] For a specific carbon material, the value obtained by dividing the number of particles N having an equivalent circle diameter of 5 μm or less out of a total number of 10,000 particles measured by the specific surface area S determined by nitrogen adsorption measurement at 77 K, that is, N / S is greater than or equal to 750 (particles·g / cm 2 ).
[0073] From the viewpoint of the input-output characteristics of the lithium ion secondary battery, N / S is preferably 900 or more, and more preferably 1200 or more.
[0074] N / S may be less than or equal to 2000, or less than or equal to 1800.
[0075] In the present disclosure, the number of particles of carbon material having an equivalent circle diameter of 5 μm or less and its ratio based on number can be measured using a wet flow particle size and shape analyzer (FPIA-3000 manufactured by Malvern) under the same conditions as the measurement of average circularity described below.
[0076] In the present disclosure, the specific surface area of the carbon material determined by nitrogen adsorption measurement at 77K can be determined using the BET method based on the adsorption isotherm obtained by nitrogen adsorption measurement at 77K.
[0077] The specific carbon material preferably satisfies the following (3).
[0078] (3) The ratio of the number of particles having an equivalent circle diameter of 5 μm or less based on the number of particles is greater than or equal to 45% with respect to the total number of 10,000 particles measured.
[0079] From the perspective of better input and output characteristics of lithium-ion secondary batteries, the above-mentioned particle number ratio of a specific carbon material is preferably greater than or equal to 45%, more preferably greater than or equal to 53%, and further preferably greater than or equal to 60%. By increasing the carbon material with an equivalent circle diameter of less than or equal to 5 μm, the solid diffusion of lithium ions moving is short, the redox reaction interface of lithium ions at the interface between the carbon material and the electrolyte increases, and there is a tendency for the current density to be easily increased.
[0080] The upper limit of the particle number ratio is not particularly limited, but is preferably 95% or less, and more preferably 90% or less, from the viewpoint that the carbon material easily satisfies the conditions (1) and (2) and the conditions (5) described later.
[0081] The specific surface area of the specific carbon material determined by nitrogen adsorption at 77K is preferably 2 m 2 / g~14m 2 / g, more preferably 3m 2 / g~8m 2 / g, more preferably 4m 2 / g~6m 2 When the specific surface area is within the above range, a good balance between the input-output characteristics and the initial charge and discharge efficiency of the lithium ion secondary battery tends to be obtained.
[0082] From the viewpoint of achieving better input / output characteristics and cycle characteristics of a lithium ion secondary battery, the specific carbon material preferably satisfies the following (4).
[0083] (4) When X is set to the equivalent circle diameter calculated on a number basis at the cumulative 99% of the particle size distribution defined as a particle size greater than or equal to 5 μm, and Y is set to the circularity at the cumulative 1% of the circularity distribution defined as a particle size greater than or equal to 5 μm, the following formula (a) is satisfied.
[0084] Y≥0.3×log 10 (X)+(0.5-0.3×log 10 6)…(a)
[0085] The right side of the above formula (a) refers to the equation of the line segment passing through the two points (particle size (μm), circularity) of (6μm, 0.5) and (50, 0.8) (it should be noted that the particle size is a logarithmic scale). Satisfying the above (4) means that the specific carbon material contains no or very small amounts of particles with small circularity (e.g., flat) and large particle size.
[0086] In certain carbon materials, Y-[0.3×log 10 (X)+(0.5-0.3×log 10 6)] is preferably greater than or equal to 0, and from the viewpoint of better input-output characteristics and cycle characteristics of the lithium ion secondary battery, can be greater than or equal to 0 and less than or equal to 0.15, and can be greater than or equal to 0 and less than or equal to 0.10.
[0087] The plane of particles with small circularity (e.g., flat shape) and large particle size is easily coordinated in parallel with the plane of the current collector. Since the parallel plane is perpendicular to the movement axis of the lithium ions, the path length of the lithium ions, electrolyte, etc. moving during charge and discharge is extended, and all the characteristics of charge and discharge are reduced. On the other hand, when the above (4) is satisfied, the flow of lithium ions and electrolyte moving in the interparticle gaps becomes smooth, and there is a tendency for the input and output characteristics and cycle characteristics of the lithium ion secondary battery to become good.
[0088] The average circularity is the average value of the circularity of each particle, and can represent the bulk powder shape, so it is effective to study it from the perspective of improving the input-output characteristics and cycle characteristics of lithium-ion secondary batteries. Therefore, by using a specific carbon material that satisfies the above (4) and the following (6), it is easy to obtain a lithium-ion secondary battery with excellent input-output characteristics and cycle characteristics.
[0089] In the present disclosure, the equivalent circle diameter of the carbon material measured on a number basis at the cumulative 99% of the distribution of particle sizes limited to greater than or equal to 5 μm and the circularity at the cumulative 1% of the circularity distribution of particle sizes limited to greater than or equal to 5 μm can be measured using a wet flow particle size and shape analyzer.
[0090] The specific carbon material preferably satisfies the following (5).
[0091] (5) Tap density is 0.80 g / cm 3 ~0.95g / cm 3 .
[0092] From the viewpoint of better input / output characteristics and energy density of lithium ion secondary batteries, the tap density of the specific carbon material is preferably greater than or equal to 0.80 g / cm 3 , more preferably greater than or equal to 0.85 / cm 3 , further preferably greater than or equal to 0.90 / cm 3 From the viewpoint of achieving a better yield of negative electrode materials and better cycle characteristics of lithium-ion secondary batteries, the tap density of the specific carbon material is preferably less than or equal to 0.95 / cm 3 .
[0093] The tap density of the carbon material tends to increase by increasing the average particle size (D50) of the carbon material, the average circularity of the carbon material, etc., or by removing flat carbon materials having large particle sizes.
[0094] In the present disclosure, the tap density of a carbon material refers to the value of: 3 Put into the capacity of 150cm 3 A graduated flat-bottom test tube (KRS-406, manufactured by Kurachi Scientific Instruments Mfg. Co., Ltd.) is plugged with a stopper and dropped 250 times from a height of 5 cm. The value is calculated based on the mass and volume of the sample powder after the drops.
[0095] From the viewpoint of achieving better input / output characteristics and cycle characteristics of a lithium ion secondary battery, the specific carbon material preferably satisfies the following (6).
[0096] (6) The average circularity is 0.90 to 0.93.
[0097] By having an average circularity greater than or equal to 0.90, it is possible to suppress the coordination of a specific carbon material in parallel with the collector plane. Thus, as the path length of lithium ions, electrolytes, etc. moving during charge and discharge becomes shorter, the flow of lithium ions and electrolytes moving in the interparticle spaces becomes smoother, and there is a tendency for the input-output characteristics and cycle characteristics of the lithium ion secondary battery to become good.
[0098] By having an average circularity of less than or equal to 0.93, since the contact between particles can be suppressed from becoming point contact, the grain boundary peeling caused by the expansion and contraction accompanying charge and discharge can be suppressed. As a result, there is a tendency for the cycle characteristics of the lithium ion secondary battery to become good. Further, in the case of obtaining a first carbon material as a raw material for a specific carbon material by spheroidization, the rough processing of the first carbon material can be reduced, so there is a tendency for the high temperature storage characteristics of the lithium ion secondary battery to become good, and in addition, since excessive spheroidization is not required, there is a tendency for the yield rate during spheroidization to also increase.
[0099] The average circularity of the specific carbon material is preferably 0.90 to 0.93, more preferably 0.905 to 0.925.
[0100] In the present disclosure, the circularity of the carbon material can be measured using a wet flow particle size and shape analyzer.
[0101] (Average surface spacing d 002 )
[0102] The average interplanar spacing d of a specific carbon material obtained by X-ray diffraction is 002 Preferably If the average surface spacing d 002 Less than or equal to There is a tendency for the initial charge and discharge efficiency and energy density of the lithium ion secondary battery to be excellent.
[0103] Average surface spacing d 002 Value This is a theoretical value of a graphite crystal, and the closer it is to this value, the higher the energy density tends to be.
[0104] Average interplanar spacing d of carbon materials 002 The value can be calculated using the Bragg formula based on the diffraction peak corresponding to the carbon 002 plane appearing near the diffraction angle 2θ=24° to 27°, by irradiating the sample with X-rays (CuKα rays), and measuring the diffraction lines using a goniometer to obtain a diffraction pattern.
[0105] Average surface spacing d 002 The measurement can be performed by X-ray diffraction. Specifically, the negative electrode material for lithium ion secondary battery is filled in the concave part of the quartz sample holder and placed on the measurement platform, and a wide-angle X-ray diffraction device (for example, manufactured by Rigaku Corporation) is used under the following measurement conditions.
[0106] Radiation source: CuKα radiation (wavelength = 0.15418nm)
[0107] Output: 40kV, 20mA
[0108] Sampling width: 0.010°
[0109] Scanning range: 10°~35°
[0110] Scanning speed: 0.5° / min
[0111] Average interplanar spacing d of carbon materials 002 The value of tends to decrease, for example, by increasing the temperature of the heat treatment when making the negative electrode material. Therefore, by adjusting the temperature of the heat treatment when making the negative electrode material, the average interplanar spacing d of the carbon material can be controlled. 002 tendency.
[0112] (R value measured by Raman spectroscopy)
[0113] The R value of the Raman spectroscopic determination of a specific carbon material is preferably 0.1 to 0.4, and from the perspective of excellent high-temperature storage characteristics of lithium-ion secondary batteries, it is more preferably 0.1 to 0.33, further preferably 0.1 to 0.3, and particularly preferably 0.1 to 0.25. If the R value is greater than or equal to 0.1, the graphite lattice defects used in the entry and exit of lithium ions are fully present, and there is a tendency to suppress the reduction of the input and output characteristics of the lithium-ion secondary battery. If the R value is less than or equal to 0.4, the decomposition reaction of the electrolyte can be fully suppressed, and there is a tendency to suppress the reduction of the initial efficiency of the lithium-ion secondary battery.
[0114] The above R value is defined as: in the Raman spectrum obtained by Raman spectrometry, 1580cm -1 The intensity of the maximum peak near 1360 cm -1 Here, the intensity ratio of the maximum peak intensity Id near 1580cm -1 The peaks appearing near 1530 cm are usually identified as peaks corresponding to the graphite crystal structure, for example, -1 ~1630cm -1 The peak observed is 1360 cm -1 The peaks appearing near are usually identified as peaks corresponding to the amorphous structure of carbon, for example, at 1300 cm -1 ~1400cm -1 Observed peak.
[0115] In the present disclosure, the measurement of the R value is performed using a Raman spectrometer (for example, XploRA PLUS, manufactured by Horiba, Ltd.), and the spectrum obtained is performed under the following conditions with the following range as a baseline.
[0116] Laser wavelength: 532nm
[0117] Laser intensity: greater than or equal to 100mW
[0118] Neutral filter: 1%
[0119] Irradiation intensity: 1mW
[0120] Measuring range: 1000cm -1 ~1800cm -1
[0121] Irradiation time: 30 seconds
[0122] Irradiation area: 1μm 2
[0123] Baseline (D band): 1100cm -1 ~1470cm -1
[0124] Baseline (G band): 1450cm -1 ~1710cm -1
[0125] Accumulated times for 1 particle: 2 times
[0126] ·Number of particles measured: 30 particles
[0127] The specific carbon material preferably does not have two or more exothermic peaks in the temperature range of 300° C. to 1000° C. in differential thermal analysis (DTA analysis) in air flow. This tends to further improve the input-output characteristics and high-temperature storage characteristics of the lithium ion secondary battery.
[0128] It should be noted that the carbon material does not have more than two exothermic peaks means that it does not have multiple identifiable exothermic peaks in the temperature range of 300°C to 1000°C, that is, it has no or one identifiable exothermic peak. Here, the so-called having multiple identifiable exothermic peaks means having multiple exothermic peaks with a peak value at least 5°C apart.
[0129] In the present disclosure, differential thermal analysis (DTA analysis) can be measured using a differential thermal and thermogravimetric simultaneous measurement device (e.g., EXSTAR TG / DTA6200 manufactured by Seiko Instruments Inc.). Specifically, α-alumina is used as a reference, and the measurement is performed at a temperature increase rate of 2.5°C / min under a flow of 300 mL / min of dry air to confirm the presence or absence of an exothermic peak of DTA at 300°C to 1000°C.
[0130] As specific carbon material and other carbon materials (hereinafter, collectively referred to as "carbon material".) It is not particularly limited, for example, graphite, low crystalline carbon, amorphous carbon, mesophase carbon, etc. can be listed. As graphite, artificial graphite, natural graphite, graphitized mesophase carbon, graphitized carbon fiber, etc. can be listed. As carbon material, from the aspect of excellent charge and discharge capacity of lithium ion secondary battery and excellent tap density, preferably spherical graphite particles, more preferably spherical artificial graphite, spherical natural graphite, etc.
[0131] In addition, by using spherical graphite particles, the agglomeration of graphite particles can be suppressed, and in the case of coating graphite particles with a carbon material having lower crystallinity (e.g., amorphous carbon), the graphite particles can be appropriately coated. Further, when a carbon material that has agglomerated during coating is used to make a negative electrode material composition, when the agglomeration of the carbon material is unravelled by stirring, the exposure of the area not coated by the above-mentioned carbon material can be suppressed. As a result, when making a lithium-ion secondary battery, there is a tendency to suppress the decomposition reaction of the electrolyte on the surface of the carbon material and suppress the reduction of the initial efficiency.
[0132] The carbon material contained in the negative electrode material may be a single type or two or more types.
[0133] As a carbon material, a first carbon material as a core and a second carbon material present on at least a portion of the surface of the first carbon material and having lower crystallinity than the first carbon material may be included. The first carbon material and the second carbon material are not particularly limited as long as the condition that the crystallinity of the second carbon material is lower than that of the first carbon material is satisfied, and for example, they may be appropriately selected from the examples of the above-mentioned carbon materials. The first carbon material and the second carbon material may be a single one, or two or more.
[0134] The presence of the second carbon material on the surface of the first carbon material can be confirmed by observation with a transmission electron microscope.
[0135] From the aspect of improving the input-output characteristics of the lithium-ion secondary battery, the second carbon material preferably includes at least one of crystalline carbon or amorphous carbon. Specifically, it is preferably selected from at least one of the group consisting of a carbonaceous substance and carbonaceous particles obtained by an organic compound (hereinafter also referred to as a precursor of the second carbon material) that can be converted into carbonaceous by heat treatment.
[0136] The precursor of the second carbon material is not particularly limited, and examples thereof include asphalt, organic polymer compounds, etc. Asphalt includes, for example, asphalt made by thermal decomposition of ethylene heavy tails, crude oil asphalt, coal tar asphalt, asphalt decomposition asphalt, polyvinyl chloride, etc., and asphalt made by polymerizing naphthalene, etc. in the presence of a super acid. As organic polymer compounds, thermoplastic resins such as polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral, natural substances such as starch, cellulose, etc., can be listed.
[0137] The carbonaceous particles used as the second carbon material are not particularly limited, and examples thereof include particles of acetylene black, oil furnace black, Ketjen black, channel black, thermal black, and soil graphite.
[0138] In the case where the carbon material includes a first carbon material and a second carbon material, the ratio of the amount of the first carbon material to the second carbon material in the carbon material is not particularly limited. From the perspective of improving the input and output characteristics of the lithium ion secondary battery, the ratio of the amount of the second carbon material in the total mass of the carbon material is preferably 0.1 mass % to 15 mass %, more preferably 1 mass % to 10 mass %, and further preferably 1 mass % to 5 mass %.
[0139] In the case of calculating based on the amount of the precursor of the second carbon material, the amount of the second carbon material in the carbon material can be calculated by multiplying the amount of the precursor of the second carbon material by its residual carbon rate (mass %). Regarding the residual carbon rate of the precursor of the second carbon material, the precursor of the second carbon material can be heat-treated alone (or in a state of a mixture of the precursor of the second carbon material and the first carbon material in a predetermined ratio) at a temperature at which the precursor of the second carbon material can become carbonaceous, and the mass of the precursor of the second carbon material before the heat treatment and the mass of the carbonaceous substance derived from the precursor of the second carbon material after the heat treatment are calculated by thermogravimetric analysis, etc.
[0140] The method for producing the negative electrode material disclosed herein is not particularly limited. From the perspective of efficiently producing a negative electrode material that satisfies the above conditions, when the carbon material is produced using the precursors of the first carbon material and the second carbon material, it is preferably produced by the following method for producing a negative electrode material.
[0141] <Method for producing negative electrode material for lithium-ion secondary battery>
[0142] The method for producing a negative electrode material for a lithium ion secondary battery according to one embodiment of the present invention may include the step of heat-treating a mixture including a first carbon material serving as a core and a precursor of a second carbon material having lower crystallinity than the first carbon material to produce a specific carbon material.
[0143] According to the above method, the above negative electrode material can be produced efficiently.
[0144] In the above method, details and preferred aspects of the first carbon material, the precursor of the second carbon material, and the specific carbon material are the same as those described in the section of the negative electrode material for lithium ion secondary batteries.
[0145] The first carbon material is preferably spherical graphite particles, more preferably spherical artificial graphite, spherical natural graphite, etc. Spherical graphite obtained by spheronizing non-spherical graphite particles such as flaky graphite particles (for example, flaky natural graphite particles) may also be used as the first carbon material.
[0146] Spheroidized graphite is obtained by subjecting non-spherical graphite particles such as flaky graphite particles to spheroidization under specific treatment conditions using a commercially available spheroidization device. Non-spherical graphite particles such as flaky graphite particles may be subjected to pulverization treatment and then spheroidization treatment as required, and the spheroidization treatment may also serve as pulverization treatment.
[0147] The lower limit of the rotor peripheral speed during the spheroidization treatment is preferably 65 m / min or more, and more preferably 70 m / min or more, from the viewpoint that D90 / D10 of the specific carbon material easily satisfies the above (1). The upper limit of the rotor peripheral speed during the spheroidization treatment is preferably 100 m / min or less, and more preferably 90 m / min or less, from the viewpoint that the specific surface area of the specific carbon material obtained by nitrogen adsorption measurement at 77 K easily satisfies the above (2).
[0148] The treatment time for the spheroidization treatment is preferably 2.0 minutes to 7.0 minutes, and more preferably 2.5 minutes to 6.0 minutes, from the viewpoint that D90 / D10 of the specific carbon material easily satisfies the above (1) and (2).
[0149] From the viewpoint that D90 / D10 of a specific carbon material easily satisfies the above (1) and (2), the product of the rotor peripheral speed and the treatment time during the spheroidization treatment is preferably 130 to 500, more preferably 150 to 450.
[0150] From the viewpoint of suppressing the electrolysis of the electrolyte in the lithium ion secondary battery and maintaining the high temperature storage characteristics, it is preferred that the specific surface area of the specific carbon material is not too high. From the viewpoint of suppressing the increase of the specific surface area that is not dependent on the particle size of the specific carbon material, it is preferred to suppress the generation of cracks and surface unevenness caused by the crushing and spheroidization of the graphite particles. Specifically, it is preferred to adjust the particle size and thickness of the graphite particles, or to spheroidize the graphite particles under the conditions of the rotor circumferential speed and processing time shown above.
[0151] The spheroidized graphite obtained by spheroidization treatment may be classified, and the spheroidized graphite from which fine powder has been removed may be used as the first carbon material. The classification method is not particularly limited, and classification by cyclone, classification by sieving, etc. may be mentioned.
[0152] The fractionation point is not particularly limited, and may be 1 μm to 10 μm, 1 μm to 5 μm, or 1 μm to 3 μm.
[0153] From the perspective of increasing the ratio of the number of particles with an equivalent circle diameter less than or equal to 5 μm based on the number basis to the total measured particle number of 10,000 and thus making it easier to satisfy the above-mentioned conditions (2) and (3), the classification point can be reduced (for example, it can be set to 1 μm to 3 μm), or the fine powder removed by classification (for example, classification by cyclone) can be further sieved to remove smaller fine powders such as less than or equal to 1 μm to obtain by-product particles, and the mixture formed by adding the by-product particles to the spherical graphite from which the fine powder has been removed is used as the first carbon material.
[0154] The graphite particles to be spheroidized are preferably natural graphite, which is a cheaper material and does not require electricity for graphitization. However, in the past, in the process of spheroidizing natural graphite, the material yield was about 30%, and since about 70% was removed, there was a problem of extremely low yield. The removed by-product graphite is mixed with resin and used as the core material of pencils, etc., but in recent years, the popularization of EV has led to a sharp increase in by-product graphite, resulting in an oversupply of by-product graphite. Therefore, it is expected to improve the material yield in the process of spheroidizing natural graphite. It should be noted that, for example, the ore in Heilongjiang Province of the People's Republic of China contains about 10% by mass of natural graphite, and there are also many ore by-products, so it is expected to improve the yield in the process of spheroidizing natural graphite.
[0155] In the method for manufacturing a negative electrode material for a lithium ion secondary battery disclosed in the present invention, the classification point can be reduced (for example, set to 1 μm to 3 μm), or the byproduct particles obtained by removing smaller micropowders less than or equal to 1 μm, etc., can be used for the first carbon material. Thus, the yield during spheroidization treatment can be improved. Furthermore, a specific carbon material easily satisfies the conditions of the above (2) and (3), and as a result, it is easy to manufacture a lithium ion secondary battery with excellent input-output characteristics and high-temperature storage characteristics.
[0156] From the perspective of improving the input-output characteristics of the lithium ion secondary battery, the temperature when the mixture is heat treated is preferably 950° C. to 1500° C., more preferably 1000° C. to 1300° C., and further preferably 1050° C. to 1250° C. The temperature when the mixture is heat treated may be fixed or variable from the start to the end of the heat treatment.
[0157] In the above method, the content of the precursor of the first carbon material and the second carbon material in the mixture before heat treatment is not particularly limited. From the aspect of improving the input and output characteristics of lithium ion secondary batteries, the content of the first carbon material is preferably 85% by mass to 99.9% by mass, more preferably 90% by mass to 99% by mass, and more preferably 95% by mass to 99% by mass, relative to the total mass of the mixture. On the other hand, from the aspect of improving the input and output characteristics of lithium ion secondary batteries, the content of the precursor of the second carbon material is preferably 0.1% by mass to 15% by mass, more preferably 1% by mass to 10% by mass, and more preferably 1% by mass to 5% by mass.
[0158] <Negative electrode for lithium-ion secondary batteries>
[0159] The negative electrode for lithium ion secondary battery disclosed in the present invention comprises a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for lithium ion secondary battery disclosed in the present invention. In addition to the negative electrode material layer and the current collector comprising the negative electrode material, the negative electrode for lithium ion secondary battery may further comprise other components as required.
[0160] The negative electrode for lithium ion secondary battery can be prepared by, for example, mixing the negative electrode material and the binder with a solvent to prepare a slurry-like negative electrode material composition, applying it to the collector to form a negative electrode material layer, or by forming the negative electrode material composition into a sheet, granular or other shape, and integrating it with the collector. Mixing can be carried out using a dispersing device such as a stirrer, a ball mill, a super sand mill, a pressure kneading machine, etc.
[0161] The binder used in the preparation of the negative electrode material composition is not particularly limited. As the binder, there can be listed styrene-butadiene copolymer, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, acrylonitrile, methacrylonitrile, hydroxyethyl acrylate, hydroxyethyl methacrylate and other ethylenically unsaturated carboxylic acid ester polymers; polymers of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; polymers with high ion conductivity such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, and polyacrylonitrile. In the case where the negative electrode material composition contains a binder, its amount is not particularly limited. The content of the binder can be, for example, 0.5 to 20 parts by mass relative to 100 parts by mass of the total of the negative electrode material and the binder.
[0162] The solvent is not particularly limited as long as it is a solvent that can dissolve or disperse the binder. Specifically, organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and γ-butyrolactone can be cited. The amount of the solvent used is not particularly limited as long as the negative electrode material composition can be made into a desired state such as a paste. The amount of the solvent used is preferably greater than or equal to 60 parts by mass and less than 150 parts by mass relative to 100 parts by mass of the negative electrode material.
[0163] The negative electrode material composition may also include a thickener. Examples of the thickener include carboxymethyl cellulose or its salt, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or its salt, alginic acid or its salt, oxidized starch, phosphorylated starch, casein, and the like. In the case where the negative electrode material composition includes a thickener, the amount thereof is not particularly limited. The content of the thickener may be, for example, 0.1 to 5 parts by mass relative to 100 parts by mass of the negative electrode material.
[0164] The negative electrode material composition may also include a conductive auxiliary material. As conductive auxiliary materials, carbon materials such as natural graphite, artificial graphite, carbon black (acetylene black, thermal black, furnace black, etc.), oxides showing conductivity, nitrides showing conductivity, etc. can be listed. In the case where the negative electrode material composition includes a conductive auxiliary material, its amount is not particularly limited. The content of the conductive auxiliary material can be, for example, 0.5 to 15 parts by mass relative to 100 parts by mass of the negative electrode material.
[0165] The material of the current collector is not particularly limited, and can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. The state of the current collector is not particularly limited, and can be selected from foil, perforated foil, net, etc. In addition, porous materials such as porous metal (foamed metal), carbon paper, etc. can also be used as the current collector.
[0166] When the negative electrode material composition is applied to the current collector to form the negative electrode material layer, the method is not particularly limited, and known methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, scraper, notch wheel coating, gravure coating, screen printing, etc. can be used. After the negative electrode material composition is applied to the current collector, the solvent contained in the negative electrode material composition is removed by drying. For example, a hot air dryer, an infrared dryer, or a combination of these devices can be used for drying. A calendering process can also be performed as needed. The calendering process can be performed by methods such as a flat press and a calendering roller.
[0167] When the negative electrode material composition formed into a sheet, granule or the like is integrated with the current collector to form the negative electrode material layer, the method of integration is not particularly limited. For example, it can be performed by a roller, a flat plate press or a combination of these means. The pressure during integration is preferably 1 MPa to 200 MPa, for example.
[0168] <Lithium-ion secondary battery>
[0169] The lithium ion secondary battery of the present disclosure includes the negative electrode for the lithium ion secondary battery of the present disclosure (hereinafter, also simply referred to as “negative electrode”), a positive electrode, and an electrolyte solution.
[0170] The positive electrode can be obtained by forming a positive electrode material layer on a current collector in the same manner as the above-mentioned method for making the negative electrode. As the current collector, a current collector obtained by forming a metal or alloy such as aluminum, titanium, stainless steel into a foil, an open-hole foil, a mesh, etc. can be used.
[0171] There is no particular limitation on the positive electrode material used to form the positive electrode material layer. For example, metal compounds (metal oxides, metal sulfides, etc.) and conductive polymer materials that can be doped or embedded with lithium ions can be listed. More specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo x Ni y Mn z O2, x+y+z=1), a composite oxide containing an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe) and other lithium-containing compounds, polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene and other conductive polymers, porous carbon, etc. The positive electrode material can be a single type or two or more types.
[0172] The electrolyte solution is not particularly limited, and for example, an electrolyte solution (so-called organic electrolyte solution) obtained by dissolving a lithium salt as an electrolyte in a non-aqueous solvent can be used.
[0173] Examples of the lithium salt include LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3, etc. The lithium salt may be a single type or two or more types.
[0174] Examples of the non-aqueous solvent include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3- Oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. The non-aqueous solvent may be a single type or two or more types.
[0175] The state of the positive electrode and the negative electrode in the lithium ion secondary battery is not particularly limited. For example, the positive electrode and the negative electrode and a separator disposed between the positive electrode and the negative electrode as required may be wound in a spiral shape, or they may be made into flat plates and stacked.
[0176] The separator is not particularly limited, for example, a nonwoven fabric, cloth, microporous membrane made of resin or a separator formed by combining them can be used. As the resin, a resin with polyolefins such as polyethylene and polypropylene as the main component can be cited. In the case where the positive electrode and the negative electrode are not in direct contact in the structure of the lithium ion secondary battery, a separator may not be used.
[0177] The shape of the lithium ion secondary battery is not particularly limited, and examples thereof include laminated batteries, paper batteries, button batteries, coin batteries, stacked batteries, cylindrical batteries, and square batteries.
[0178] The lithium ion secondary battery disclosed herein is suitable as a large-capacity lithium ion secondary battery used in electric vehicles, power tools, power storage devices, etc. It is particularly suitable as a lithium ion secondary battery used in electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., which require charging and discharging at a large current in order to improve acceleration performance and braking regeneration performance.
[0179] Example
[0180] Hereinafter, the present invention will be specifically described based on the following test results, but the present invention is not limited to these test results.
[0181] [Example 1]
[0182] (Preparation of spheroidized natural graphite)
[0183] A spheroidizing treatment device (Hybridization NHS-0, Nara Machinery Manufacturing Co., Ltd.) was used to spheroidize flaky natural graphite (produced in Heilongjiang Province, China) with an average particle size of 50 μm under the conditions of a rotor peripheral speed of 75.0 m / min for 2.5 minutes to produce spheroidized natural graphite. A cyclone-type classifier was used and the classification point was set to 1 μm, and the produced spheroidized natural graphite was cyclone-classified.
[0184] [Example 2]
[0185] Using a spheroidizing treatment device (Nara Machinery, Hybridization NHS-0), a spheroidizing treatment was performed on a flaky natural graphite (produced in Heilongjiang Province, China) with an average particle size of 50 μm under the conditions of a rotor circumferential speed of 85.0 m / min and 3.0 minutes to produce spheroidized natural graphite. A cyclone-type classifier was used and the classification point was set to 10 μm to perform cyclone classification on the produced spheroidized natural graphite. For the particles removed by cyclone classification, particles less than or equal to 1 μm were further removed by screening to obtain by-product particles. 30 parts by mass of the obtained by-product particles were mixed with 70 parts by mass of the spheroidized natural graphite (main particles in Table 1) obtained by cyclone classification to obtain the spheroidized natural graphite used in the production of the negative electrode material.
[0186] (Manufacturing of negative electrode materials)
[0187] A negative electrode material was prepared in the same manner as in Example 1, except that the spheroidized natural graphite obtained in Example 2 was used instead of the spheroidized natural graphite obtained in Example 1.
[0188] [Examples 3, 4, 7, 8]
[0189] Spheroidized natural graphite was obtained in the same manner as in Example 1 except that the flaky natural graphite used in Example 1 was changed to the one shown in Table 1 or the conditions of the spheroidization treatment were changed as shown in Table 1.
[0190] (Manufacturing of negative electrode materials)
[0191] A negative electrode material was prepared in the same manner as in Example 1 except that the spheroidized natural graphite obtained in Example 3, 4, 7 or 8 was used instead of the spheroidized natural graphite obtained in Example 1.
[0192] [Examples 5, 6, and 9]
[0193] The scaly natural graphite used in Example 2 was changed to the material shown in Table 1, or the conditions of the spheroidization treatment were changed as shown in Table 1. Cyclone classification was performed in the same manner as in Example 2 to obtain by-product particles. The obtained by-product particles and the spheroidized natural graphite obtained by cyclone classification were mixed in the ratio shown in Table 1 to obtain spheroidized natural graphite used in the preparation of the negative electrode material.
[0194] (Manufacturing of negative electrode materials)
[0195] A negative electrode material was prepared in the same manner as in Example 2, except that the spheroidized natural graphite obtained in Example 5, 6 or 9 was used instead of the spheroidized natural graphite obtained in Example 2.
[0196] [Comparative Examples 1, 2, and 4]
[0197] Spheroidized natural graphite was obtained in the same manner as in Example 1 except that the conditions of the spheroidization treatment in Example 1 were changed as shown in Table 1.
[0198] (Manufacturing of negative electrode materials)
[0199] A negative electrode material was prepared in the same manner as in Example 1, except that the spheroidized natural graphite obtained in Comparative Example 1, 2 or 4 was used instead of the spheroidized natural graphite obtained in Example 1.
[0200] [Comparative Example 3]
[0201] By-product particles were obtained by cyclone classification in the same manner as in Example 2 except that the conditions for the spheroidization treatment in Example 2 were changed as shown in Table 1. 30 parts by mass of the obtained by-product particles and 70 parts by mass of spheroidized natural graphite obtained by cyclone classification were mixed to obtain spheroidized natural graphite used in the preparation of the negative electrode material.
[0202] Table 1 shows the spheroidization conditions, cyclone classification conditions, and by-product particle addition conditions in each of the Examples and Comparative Examples.
[0203] For the negative electrode material obtained in each embodiment and comparative example, the tap density is measured by the following method, the D90 / D10 is measured, the average particle size (50%D) is measured, the average circularity is measured, the N2 specific surface area is measured, the average surface spacing, the R value, the exothermic peak, the equivalent circle diameter is less than or equal to the number of particles of 5 μm and the ratio thereof, the equivalent circle diameter is measured on a number basis when the cumulative 99% of the particle size distribution of the particle size of 5 μm or more is defined, and the circularity is measured when the cumulative 1% of the circularity distribution of the particle size of 5 μm or more is defined. The results are shown in Tables 2 and 3.
[0204] It should be noted that the “border value of circularity obtained from the measured value of the equivalent circle diameter and formula (a)” in Table 3 refers to the value on the right side when the equivalent circle diameter calculated on a number basis at a cumulative 99% is substituted into formula (a).
[0205] [Determination of tap density]
[0206] The sample powder is 100cm 3 Input capacity 150cm 3 A graduated flat-bottomed test tube (KRS-406 manufactured by Kurachi Scientific Instruments Manufacturing Co., Ltd.) was plugged with a stopper. The graduated flat-bottomed test tube was dropped 250 times from a height of 5 cm, and the value obtained from the mass and volume of the sample powder after the drop was defined as the tap density. The results are shown in Table 2.
[0207] [Measurement of average particle size (D50), D10, D90 and D90 / D10]
[0208] 0.06 g of the negative electrode material and distilled water containing 0.2% by mass of a surfactant (trade name: LIPONOL T / 15, manufactured by Lion Co., Ltd.) were added to a test tube (12 mm×120 mm, manufactured by Maruemu Co., Ltd.), and stirred for 20 seconds using a test tube oscillator (Pasolina NS-80, manufactured by AS ONE Co., Ltd.) to obtain a liquid in which the negative electrode material is dispersed. The liquid was added to the sample water tank of a laser diffraction particle size distribution measuring device (SALD-3100, manufactured by Shimadzu Corporation). Next, ultrasonic waves were applied to the liquid while it was circulated with a pump (the pump flow rate was from the maximum value to 65%), and the amount of water was adjusted so that the absorbance became 0.10 to 0.15, and the volume cumulative 50% particle size (D50) of the obtained particle size distribution was taken as the average particle size. Furthermore, D90 / D10 was determined from the volume cumulative 10% particle size (D10) of the obtained particle size distribution and the volume cumulative 90% particle size (D90) of the obtained particle size distribution.
[0209] [Measurement of average circularity and circularity at cumulative 1% of circularity distribution defined as particle size greater than or equal to 5 μm]
[0210] The circularity of the negative electrode material was measured using a wet flow particle size and shape analyzer (FPIA-3000 manufactured by Malvern Co., Ltd.), and the average circularity as the cumulative 50% circularity on a number basis and the circularity at the cumulative 1% of the circularity distribution limited to particles of 5 μm or more were determined.
[0211] The measurement temperature was 25° C., the concentration of the measurement sample was 10% by mass, and the number of particles counted was 10000. Water was used as a solvent for dispersion.
[0212] As a pretreatment for this determination, 0.06 g of carbon material and distilled water containing a surfactant (trade name: LIPONOL T / 15, manufactured by Lion Co., Ltd.) at a mass ratio of 0.2% were added to a test tube (12 mm × 120 mm, manufactured by Maruemu Co., Ltd.), stirred for 20 seconds using a test tube oscillator (Pasolina NS-80, manufactured by AS ONE Co., Ltd.), and then stirred for 1 minute using ultrasound. As an ultrasonic cleaning machine, US102 manufactured by SND Co., Ltd. (high-frequency output power 100 W, oscillation frequency 38 kHz) was used. The results are shown in Tables 2 and 3.
[0213] [Determination of N2 specific surface area]
[0214] The N2 specific surface area was calculated by measuring nitrogen adsorption at liquid nitrogen temperature (77 K) using a high-speed specific surface area / pore distribution measuring device (FlowSorb III, manufactured by Shimadzu Corporation) using a single-point method. The results are shown in Table 2.
[0215] [Average surface spacing, R-value and heat peak]
[0216] The average interplanar spacing, R value and exothermic peak of the negative electrode materials obtained in each example and comparative example were measured by the above-mentioned method. The results are shown in Table 2.
[0217] In Table 2, regarding the negative electrode materials obtained in each of the examples and comparative examples, there is one exothermic peak in the DTA at 300° C. to 1000° C.
[0218] [Determination of the number and proportion of particles with an equivalent circle diameter of 5 μm or less]
[0219] The number of particles with an equivalent circle diameter of less than or equal to 5 μm and their proportion of the negative electrode material were measured under the same conditions as the average circularity measurement conditions using a wet flow particle size and shape analyzer (FPIA-3000 manufactured by Malvern). Further, the proportion of the number of particles with an equivalent circle diameter of less than or equal to 5 μm / total measured count was calculated based on the number of particles with an equivalent circle diameter of less than or equal to 5 μm and the proportion in the total measured count (10,000 in the case of this embodiment). The results are shown in Table 3.
[0220] [Number of particles with equivalent circle diameter less than or equal to 5 μm / N2 specific surface area]
[0221] The number of particles with an equivalent circle diameter of 5 μm or less / N2 specific surface area was calculated using the N2 specific surface area calculated as described above and the number of particles with an equivalent circle diameter of 5 μm or less.
[0222] [Equivalent circle diameter (μm) at the cumulative 99% of the particle size distribution of 5 μm or more based on number]
[0223] Using a wet flow particle size and shape analyzer (FPIA-3000 manufactured by Malvern), the equivalent circle diameter (μm) on a number basis at the cumulative 99% of the particle size distribution limited to a particle size of 5 μm or more was measured under the same conditions as the average circularity measurement conditions. The results are shown in Table 3.
[0224] [Calculation of the boundary value of circularity from the measured value of the equivalent circle diameter and formula (a)]
[0225] The value on the right side of formula (a) was calculated by substituting the cumulative 99% equivalent circle diameter (μm) of the particle size distribution of particles greater than or equal to 5 μm measured as described above into X in formula (a) to obtain the boundary value of circularity. The results are shown in Table 3.
[0226] [Difference between the circularity at the cumulative 1% of the circularity distribution defined as a particle size of 5 μm or more and the boundary value of the circularity]
[0227] The difference between the circularity measured as described above at the cumulative 1% of the circularity distribution limited to a particle size of 5 μm or more and the boundary value of the circularity calculated as described above was obtained. When the value of the difference is greater than or equal to 0, the condition of formula (a) is satisfied. The results are shown in Table 3.
[0228] [Table 1]
[0229]
[0230] [Table 2]
[0231]
[0232] [Table 3]
[0233]
[0234] (Preparation of lithium-ion secondary battery for evaluation of input-output characteristics)
[0235] Using the negative electrode materials prepared in the respective Examples and Comparative Examples, lithium ion secondary batteries for evaluating input-output characteristics were prepared in the following manner.
[0236] First, an aqueous solution of CMC (carboxymethyl cellulose, manufactured by Daicel Fine Chemicals, Ltd., product number 2200) as a thickener is added (CMC concentration: 2% by mass) to 98 parts by mass of the negative electrode material in such a manner that the solid content of CMC becomes 1 part by mass, and kneading is performed for 10 minutes. Next, distilled water is added in such a manner that the total solid content concentration of the negative electrode material and CMC becomes 40% to 50% by mass, and kneading is performed for 10 minutes. Next, an aqueous dispersion of SBR (BM400-B, ZEON Co., Ltd., Japan) of styrene butadiene copolymer rubber as a binder is added (SBR concentration: 40% by mass) in such a manner that the solid content of SBR becomes 1 part by mass, and mixing is performed for 10 minutes to prepare a paste-like negative electrode material composition. Next, a coating amount per unit area is made to be 10.0 mg / cm 2 The negative electrode material composition was coated on an electrolytic copper foil with a thickness of 11 μm using a notch wheel coater with a gap adjusted in a manner to form a negative electrode material layer. Then, the electrode density was adjusted to 1.65 g / cm using a hand press. 3 The electrolytic copper foil on which the negative electrode material layer was formed was punched out into a disk shape having a diameter of 14 mm to prepare a sample electrode (negative electrode).
[0237] The sample electrode (negative electrode), separator, and counter electrode (positive electrode) are placed in a coin-type battery container in the order of the prepared sample electrode (negative electrode), and the electrolyte is injected to prepare a coin-type lithium-ion secondary battery. As an electrolyte, the following electrolyte is used, namely: 0.5 mass% of vinylene carbonate (VC) is added to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (the volume ratio of EC to EMC is 3:7) relative to the total amount of the mixed solution, and LiPF6 is dissolved in a manner to obtain an electrolyte of 1 mol / L. As a counter electrode (positive electrode), metallic lithium is used. As a separator, a polyethylene microporous membrane with a thickness of 20 μm is used. Using the prepared lithium-ion secondary battery, the initial charge and discharge characteristics and the input characteristics (DCR) are evaluated by the following method.
[0238] [Evaluation of input and output characteristics]
[0239] (Evaluation of initial charge and discharge characteristics)
[0240] The prepared lithium ion secondary battery was charged at a constant current of 0.2C until the voltage reached 0V (V vs. Li / Li + ), and then constant voltage charging was performed at 0 V until the current value reached 0.02 C. The capacity at this time was taken as the initial charge capacity.
[0241] Then, after a 30-minute rest, the battery was discharged at a constant current of 0.2C until the voltage reached 1.5V (V vs. Li / Li +). The capacity at this time is regarded as the initial discharge capacity (the discharge capacity in Table 4).
[0242] The results are shown in Table 4.
[0243] In addition, "C" used as the unit of current value means "current value (A) / battery capacity (Ah)".
[0244] The direct current resistance (DCR) of the lithium ion secondary battery was measured to determine the output density of the battery. The details are as follows.
[0245] In addition, Table 4 shows the results.
[0246] (Measurement of DCR at 25°C)
[0247] The lithium ion secondary battery was placed in a thermostatic chamber set at 25° C., and charged and discharged for one cycle under the conditions of charge: CC / CV 0.2C0V0.02C Cut, and discharge: CC 0.2C 1.5V Cut.
[0248] Next, constant current charging was performed at a current value of 0.2 C until the SOC reached 50%.
[0249] The lithium ion secondary battery was placed in a thermostatic chamber set at 25°C and charged at 1C, 3C and 5C for 10 seconds each. The voltage drop (ΔV) at each constant current was measured, and the DC resistance (DCR) was measured using the following formula.
[0250] DCR[Ω]={(3C voltage drop ΔV-1C voltage drop ΔV)+(5C voltage drop ΔV-3C voltage drop ΔV)} / 4
[0251] (Preparation of lithium-ion secondary battery for evaluation of cycle characteristics)
[0252] Using the negative electrode materials prepared in each of the Examples and Comparative Examples, lithium ion secondary batteries for evaluating cycle characteristics were prepared in the following manner.
[0253] First, 7 mass parts of carbon-coated SiO (heat treatment temperature: 1000°C, carbon coating amount: 5 mass%) were added to 93 mass parts of the negative electrode material prepared in each embodiment and each comparative example as the negative electrode material, and mixed for 10 minutes to prepare a negative electrode active material. An aqueous solution of CMC (carboxymethyl cellulose, Daiichi Kogyo Seiyaku Co., Ltd., Serogen WS-C) as a thickener was added in such a manner that the solid content of CMC became 1 mass part, and kneading was performed for 10 minutes. Next, distilled water was added in such a manner that the total solid content concentration of the negative electrode material and CMC became 40 mass% to 50 mass%, and kneading was performed for 10 minutes. Next, an aqueous dispersion of SBR (BM400-B, ZEON Co., Ltd., Japan) as a binder (SBR concentration: 40% by mass) was added in such a manner that the solid content of SBR was 1 part by mass, and mixed for 10 minutes to prepare a paste-like negative electrode material composition. Next, a coating amount per unit area of 10.0 mg / cm 2 The negative electrode material composition was coated on an electrolytic copper foil with a thickness of 11 μm using a notch wheel coater with a gap adjusted in a manner to form a negative electrode material layer. Then, the electrode density was adjusted to 1.65 g / cm using a roller press. 3 The electrolytic copper foil on which the negative electrode material layer was formed was punched out into a size of 4.0 cm×3.0 cm to prepare a sample electrode (negative electrode).
[0254] As a positive electrode, a positive electrode composed of NMC was cut out with the same area, and a separator (porous polyethylene film) was placed between the negative electrode and the positive electrode and combined. As an electrolyte, the following electrolyte was used, namely: 0.5 mass% vinylene carbonate (VC) and 1.0 mass% fluoroethylene carbonate (FEC) were added to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (the volume ratio of EC to EMC was 3:7) relative to the total amount of the mixed solution, and LiPF6 was dissolved in a manner to become a concentration of 1 mol / L.
[0255] [Evaluation of cycle characteristics]
[0256] In each of the Examples and Comparative Examples, the lithium ion battery produced as described above was used, and the cycle characteristics were evaluated in the following manner.
[0257] First, constant current charging was performed at 25°C with a current value of 0.2C and a charge termination voltage of 4.2V. When the current value reached 4.2V, constant voltage charging was performed at this voltage until the current value reached 0.02C. After a 30-minute rest, constant current discharge was performed twice at 25°C with a current value of 0.2C and a termination voltage of 2.7V for aging. Then, after the first cycle of charge and discharge was performed under the above-mentioned charge and discharge conditions, the current value was set to 1.0C, and a cycle test of 99 cycles was performed, and a total of 100 cycles of cycle tests were performed.
[0258] The discharge capacity retention rate (%) after 100 cycles (cycle retention rate in Table 4) was calculated according to the following formula.
[0259] Discharge capacity retention rate (%) = (discharge capacity after 100 cycles / discharge capacity at the first cycle) × 100
[0260] [Evaluation of liquid injection properties]
[0261] The negative electrode for the above cycle characteristics evaluation was prepared and the electrode density was adjusted to 1.65 g / cm by a roller press. 3 The pressed negative electrode is punched into A circular electrode was attached to a glass substrate with double-sided tape to form a flat electrode surface without warping. 3 μL PC (polycarbonate: manufactured by Kishida Chemical Co., Ltd.) was dripped into the center of the negative electrode using a micropipette, and the injection time until penetration was measured. Three identical electrodes were prepared and the average value of the three measurements was calculated. The results are shown in Table 4.
[0262] (Preparation of lithium-ion secondary battery for evaluation of electrode orientation)
[0263] A negative electrode for a lithium ion secondary battery was produced in the same manner as described above (production of a lithium ion secondary battery for evaluation of input-output characteristics), and the electrode orientation was evaluated under the conditions shown below.
[0264] [Evaluation of electrode orientation]
[0265] The obtained negative electrode for lithium ion secondary battery was formed into a 5 cm wide and 600 cm area. 2The long strip sheet is pressed with a roller press at an oil pressure of 4t. The linear pressure at this time is 4t / 5cm=0.8t / cm. The pressed negative electrode is set in an X-ray diffraction measurement unit, and an X-ray diffraction measurement device (X-RAY DIFFRACTIOMETER MultiFlex, manufactured by Rigaku Corporation) is used. Under the conditions of a scanning speed of 0.25° / min, a tube voltage of 40kV, a tube current of 30mA, a divergence slit of 1°, a scattering slit of 1°, and a light receiving slit of 0.3mm, CuKα rays are used to measure the X-ray diffraction pattern (2θ=25.5°~27.5°, 76.5°~78.5°). The peak intensity (I 002 ) and the peak intensity of the 110 diffraction line (I 110 ) is the ratio of I 002 / I 110 The results are shown in Table 4.
[0266] [High temperature storage maintenance rate]
[0267] As step 1, a lithium ion secondary battery prepared in the same manner as in the above (preparation of a lithium ion secondary battery for evaluation of input-output characteristics) was placed in a thermostatic chamber set at 25° C. and charged at a constant current value of 0.2 C until the voltage reached 0 V (V vs. Li / Li + ), and then constant voltage charging was performed at 0 V until the current value reached 0.02 C. Then, after a 30-minute rest, constant current discharge was performed at a current value of 0.2 C until the voltage reached 1.5 V (V vs. Li / Li + After repeating this charge and discharge twice, constant current charging was performed at a current value of 0.2C until the voltage reached 0V (V vs. Li / Li + ), then constant voltage charging was performed at 0 V until the current value reached 0.02 C, and the battery was placed in a constant temperature chamber set at 60° C. and stored for 7 days.
[0268] Then, as step 2, the lithium ion secondary battery was placed in a thermostatic chamber set at 25° C. for 60 minutes and discharged at a constant current value of 0.2 C until the voltage reached 1.5 V (V vs. Li / Li + ). Next, charge and discharge were repeated once under the above conditions. The 60° C. storage (step 1) and the capacity confirmation after storage (step 2) were repeated 3 times in total.
[0269] The high-temperature storage retention rate was calculated according to the following formula, and the arithmetic mean value was defined as the high-temperature storage property (%).
[0270] High temperature storage retention rate (%) = (first discharge capacity at 25°C after storage at 60°C for 21 days) / (second discharge capacity at 25°C before storage at 60°C) × 100
[0271] [Table 4]
[0272]
[0273] If Example 2 and Comparative Example 3 are compared, D50 is about 18 μm and N2 specific surface area is about 6 m 2 / g, both are the same, but the DCR during charging is low in Example 2 and is improved. It is believed that Example 2 has a higher average circularity than Comparative Example 3, so the DCR result is better due to the effect of the average circularity. However, when the comparison is also made including Comparative Example 2, which has a higher average circularity and a smaller D50, it is shown that the input characteristics cannot be fully improved only by a small D50, a large N2 specific surface area, and a high average circularity.
[0274] As a result of in-depth research, it is known that by increasing the number of particles with an equivalent circle diameter less than or equal to 5μm and adjusting the composition of coarse powder and fine powder, D90 / D10 is set to a specific range to further improve the input characteristics of lithium-ion secondary batteries. It is believed that by increasing the number of particles with an equivalent circle diameter less than or equal to 5μm, there are a large number of particles with a short distance of solid diffusion in each particle, and these particles also play the role of a conductive material between other particles. It is believed that the flow of current in the negative electrode is dispersed and low-resistance, which not only obtains good input characteristics but also obtains good cycle characteristics. Further, increasing the number of particles with an equivalent circle diameter less than or equal to 5μm per unit N2 specific surface area, that is, the number of particles with an equivalent circle diameter less than or equal to 5μm / N2 specific surface area, means that the conductivity can be improved and the solid diffusion can be shortened without increasing the reaction area between the negative electrode material and the electrolyte. It is therefore believed that compared with the case where the N2 specific surface area is increased by simply increasing the number of particles having an equivalent circle diameter of 5 μm or less, the consumption of the electrolyte is reduced, thereby obtaining better cycle characteristics.
[0275] If D90 / D10 is within a specific range, the distance from one surface in the thickness direction to another surface through the gap inside the negative electrode material layer, i.e., the length of the curved path, will not be too long, and there is a tendency for the liquid flow to become good. Thus, it is not easy to produce an area where the electrolyte and the negative electrode material cannot contact, and it is easy to maintain good cycle characteristics.
[0276] On the other hand, if D90 / D10 is greater than a specific value, the length of the curved path becomes longer due to the large particle size particles, which deteriorates the liquid flow. It is believed that, for example, in Comparative Example 3, compared with each embodiment and each comparative example, the injection time is the longest and the electrode orientation is also the highest value, so the length of the curved path becomes longer. It is therefore believed that in Comparative Example 3, although the number of particles with an equivalent circle diameter of less than or equal to 5 μm / N2 specific surface area that contributes to the cycle characteristics is larger than that of Example 9, the injection time is long, so the cycle characteristics are worse than those of Example 9.
[0277] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described as being incorporated by reference.
Claims
1. A negative electrode material for a lithium ion secondary battery, comprising a carbon material satisfying the following (1) and (2), (1) D90 / D10 of the volume-based particle size is greater than 2.0 and less than 4.3; (2) The value obtained by dividing the number of particles N with an equivalent circle diameter of 5 μm or less out of the total number of particles measured (10,000 particles) by the specific surface area S determined by nitrogen adsorption measurement at 77 K, that is, N / S is greater than or equal to 750 (particles·g / cm 2 ).
2. The negative electrode material for lithium ion secondary battery according to claim 1, wherein the carbon material satisfies the following (3): (3) The ratio of the number of particles having an equivalent circle diameter of 5 μm or less based on the number of particles is greater than or equal to 45% with respect to the total number of 10,000 particles measured.
3. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the carbon material satisfies the following (4): (4) When X is the equivalent circle diameter on a number basis at the cumulative 99% of the particle size distribution defined as a particle size of 5 μm or more, and Y is the circularity at the cumulative 1% of the circularity distribution defined as a particle size of 5 μm or more, the following formula (a) is satisfied: Y≥0.3×log 10 (X)+(0.5-0.3×log 10 6)…(a)。 4. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the carbon material satisfies the following (5): (5) Tap density is 0.80 g / cm 3 ~0.95g / cm 3 .
5. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the carbon material satisfies the following (6): (6) The average circularity is 0.90 to 0.
93.
6. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the average interplanar spacing d of the carbon material obtained by X-ray diffraction is 002 for 7 . The negative electrode material for a lithium ion secondary battery according to claim 1 , wherein the carbon material has an R value of 0.1 to 0.4 as determined by Raman spectroscopy.
8. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the specific surface area of the carbon material determined by nitrogen adsorption at 77K is less than or equal to 14 m 2 / g. 9 . The negative electrode material for a lithium ion secondary battery according to claim 1 , wherein the carbon material does not have two or more exothermic peaks in a temperature range of 300° C. to 1000° C. in differential thermal analysis in an air flow. 10 . A negative electrode for a lithium ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium ion secondary battery according to claim 1 or 2. 11 . A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to claim 11 , a positive electrode and an electrolyte.
